Effect of Microencapsulation on Survivability of Bifidobacterium bifidum in Probiotic Yoghurt - V.P Sruthi; R. Geetha; C.T Sathian; A.S Lejaniya (The Indian Veterinary Journal, 2023)
The main objective of the study was to assess the effect of microencapsulation on viability and fermentation potential of Bifidobacterium bifidum in probiotic yoghurt. Extrusion method was used in the study. The study observed that there was significant difference between the viability of B. bifidum in free cells and microencapsulated cells. We also investigated the impact of fermentation on the viability of both encapsulated and free cells of Bifidobacterium bifidum in probiotic yogurt, as well as its subsequent storage stability. The encapsulated B. bifidum was maintained the viability throughout the storage. Acidity was comparatively low in treatment samples. Same pattern observed in pH also. The overall sensory scores of fresh control probiotic yoghurt (C) and treatment (T) yoghurt prepared encapsulated B. bifidum were 17.62±0.44 and 18.02±0.44 respectively. There was no significant difference (p